Systematic Literature Review : Dampak Kendaran Over Dimension Over Load (ODOL) terhadap Umur Rencana Jalan Arteri di Indonesia - Naila Savira; Dina Nur Halimah; I Ketut Yogi Yudyantara (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2026)
Over-Dimension Over-Load (ODOL) vehicles are transport vehicles with dimensions or loads exceeding permitted technical limits, potentially causing axle loads to surpass the Maximum Axle Load (MST) for specific road classes. This study aims to examine the characteristics of ODOL axle loads, the increase in the Vehicle Damage Factor (VDF), and the resulting impact on the reduction of road design life. The Systematic Literature Review (SLR) methodology is used to analyze 10 selected articles based on three Quality Assessment criteria. The review reveals that eight articles utilized technical methods—such as AASHTO 1993, VDF, ESAL, Cumulative Equivalent Standard Axle (CESA), MDPJ 2017, and axle load simulations—while three articles explicitly addressed arterial or national roads. ODOL vehicles were shown to increase road damage potential, evidenced by VDF/CESA increases of up to 169.53%. Consequently, road design life decreased by 1.96 to 7.45 years; in certain simulations, the service life dropped from 20 years to just 3.65 years. These findings underscore the importance of load monitoring via weighbridges and Weigh-in-Motion (WIM) systems, as well as "Zero ODOL" policies, in maintaining the sustainability of road services.